2007
DOI: 10.1021/jp070155u
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Interface on Biomass Burn Tar Balls Determined by Single Particle Scanning Transmission X-ray Microscopy

Abstract: Carbonaceous particles originating from biomass burning can account for a large fraction of organic aerosols in a local environment. Presently, their composition, physical and chemical properties, as well as their environmental effects are largely unknown. Tar balls, a distinct type of highly spherical carbonaceous biomass burn particles, have been observed in a number of field campaigns. The Yosemite Aerosol Characterization Study that took place in summer 2002 occurred during an active fire season in the wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
157
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(177 citation statements)
references
References 51 publications
15
157
0
Order By: Relevance
“…Particle elemental composition was quantified and is reported in units of atomic fractions. More details on CCSEM/EDX analysis and X-ray mapping of particles are reported elsewhere 11,12,31,34,35 . An FEI Titan environmental transmission electron microscope (TEM, FEI) operated at 300 kV was used to perform high-resolution TEM imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Particle elemental composition was quantified and is reported in units of atomic fractions. More details on CCSEM/EDX analysis and X-ray mapping of particles are reported elsewhere 11,12,31,34,35 . An FEI Titan environmental transmission electron microscope (TEM, FEI) operated at 300 kV was used to perform high-resolution TEM imaging.…”
Section: Methodsmentioning
confidence: 99%
“…51 Analysis of NEXAFS spectra provide chemical composition and mixing states of individual particles with spatial resolution of B30 nm. [52][53][54][55][56] Acquired carbon K-edge spectra allow identification of the organic carbon, elemental carbon (i.e. soot), and overall contribution of inorganic components within individual particles.…”
Section: Chemical Imaging Of Individual Inpmentioning
confidence: 99%
“…In the literature the C / O atomic ratio in atmospheric tar balls varies widely. Several studies established high C / O ratios (7-10) (Pósfai et al, 2003(Pósfai et al, , 2004Hand et al, 2005;Niemi et al, 2006;Adachi and Buseck, 2011), whereas others found some tar balls with significantly lower C / O ratios in the range of 1-2 (Tivanski et al, 2007;China et al, 2013).…”
mentioning
confidence: 99%
“…It should be stressed that tar-ball particles might undergo aging processes in the atmosphere resulting in a significantly enhanced oxygen ratio in the outermost layer of the particles at a thickness of 30-40 nm (Hand et al, 2005;Tivanski et al, 2007;China et al 2013). During their long range atmospheric transport tar-ball particles occasionally form aggregates with up to 10 particles, including coagulation with dust particles (Hand et al, 2005;Deboudt et al, 2010).…”
mentioning
confidence: 99%